Glutamine Metabolism in Both the Oxidative and Reductive Directions Is Triggered in Shrimp Immune Cells (Hemocytes) at the WSSV Genome Replication Stage to Benefit Virus Replication - He, Shu-Ting; Lee, Der-Yen; Tung, Cheng-Yi; Li, Chun-Yuan; Wang, Han-Ching (Frontiers in Immunology, 2019)
White spot syndrome virus (WSSV) is the causative agent of a shrimp disease that has caused huge global economic losses. Although its pathogenesis remains poorly understood, it has been reported that in the shrimp immune cells (hemocytes) targeted by WSSV, the virus triggers both the Warburg effect and glutamine metabolism at the WSSV genome replication stage (12 h post infection). Glutamine metabolism follows two pathways: an oxidative pathway mediated by α-KGDH (α-ketoglutarate dehydrogenase) and an alternative reductive pathway mediated by IDH1 and IDH2 (isocitrate dehydrogenase 1 and 2). Here we used isotopically labeled glutamine ([U-13C]glutamine and [1-13C]glutamine) as metabolic tracers to show that, at the replication stage, both the oxidative and reductive glutamine metabolic pathways were activated. We further show that the mRNA expression levels of α-KGDH and IDH1 were increased in WSSV-infected shrimps and that silencing of α-KGDH, IDH1 and IDH2 with their respective dsRNAs led to a decrease in WSSV gene expression and WSSV replication. Taken together, our findings provide new evidence for WSSV-induced metabolic reprogramming in hemocytes and demonstrate its importance in virus replication.